Frederick Wiseman - Atkins, Thomas R. 1939- (New York Monarch Press, 1976)
The films of Frederick Wiseman, unparalleled as social and artistic documents of U.S. institutional life, have earned him international acclaim and generated continued controversy. His career and remarkable series of documentaries, beginning with the now famous Titicut Follies to such recent work as Juvenile Court, Primate, and Welfare, are covered in a collection of critical essays, interviews, reviews, complete filmography, and selective bibliography. Called by Pauline Kael "the most sophisticated intelligence to enter the documentary field in recent years," Frederick Wiseman has by his humanistic pursuit of truth, become a major figure in contemporary cinema.
Bibliography: pages 133-134.
Filmography: pages 127-131.
A gift of Ms. Jane Hofileña.
Keywords: Wiseman, Frederick; Wiseman, Frederick